Vendo minha imagem: Paulo Nazareth e arte for sale - Rafael Perpétuo de Souza (2021)
This dissertation presents through qualitative analyses, how events of the life of visual artist Paulo Nazareth influenced the production of his artwork and how he developed a unique relationship with the primary art market that consumes his production. From his Amerindian, black and peripheral origins, through events and residencies that led him to autobiography himself as a person “that lives around the world”, through his studies as an artist at the Escola de Belas Artes of UFMG, it is possible to perceive by textual analysis and artworks, how Nazareth develops a coherent and current thought. We dig deep into Paulo Nazareth’s artistic practices and research methods, seeking both in the unique technicality of his artwork, as well as in the ways of selection and collecting objects to produce his body of artworks. Finally, we developed a thought on top of the term coined by the artist, for sale, which is the conceptual basis of all of his relationship with the market and main object of this study. This gives us support to reflect on the construction of its own artistic trajectory as a unique model, generating a conceptualization of this in the field of visual arts.